Semiotic Study and the Value of Islam in Oral Tradition of Sariga in Muna Society of South Sulawesi Province - Saidiman; Sumiyadi; Iskandar Wassid; Tedi Parmadi (Proceeding International Conference on Malay Identity, 2020)
This study examines semiotic study and the value of islam in oral tradition of Sariga in Muna society of south Sulawesi Province.??. Semiotic meaning and islamic values ??in the Muna community are widely applied through local traditions in the community and one of them is the oral tradition of Sariga. The problem in this study is "What meaning of semiotics and islamic values ??are contained in the Sariga oral tradition of the Muna tribe in Southeast Sulawesi?" The purpose of this study is to describe meaning of semiotics and islamic values ??contained in the Sariga oral tradition of the Muna tribe in Southeast Sulawesi. The method used is the ethnographic method and the method of cultural research. Theories used in this research are semiotic theory, value theory, value theory in Islamic religion, oral tradition theory, and cultural theory. The results showed that meaning semiotic in the oral tradition of Sariga in the Muna society that every material or equipment used during the procession of the Sariga oral tradition, is not only material/tool without meaning, but every material used also has a specific meaning/function for the community. The Islamic values ??in the oral tradition of Sariga in the Muna community contained Divine value, Religious value, Human value, Ethical value, and Aesthetic value. Keywords: Semiotic, Value, Islamic Religion, Oral Sariga Tradition, Muna Tribe.